Book Review - Breaking the Barriers Changing the Way We Support the Physical and Mental Health of Police Officers - Weatherford, Steven (International Journal of Police Science, 2024)
In Breaking the Barriers Changing the Way We Support the Physical and Mental Health of Police Officers, Ronald A Rufo, EdD, uses personal stories as well as interviews with fellow officers and mental health providers to explain how the police culture and calls police officers handle in their careers create stress and mental health issues. Rufo identifies the responses to those stressors and solutions to address the identified mental health challenges. The book closes with thoughts and recommendations from many of the police officers and mental health professionals interviewed for the book. In the last few years, law enforcement administrators, mental health providers, and legislatures have placed a higher priority on addressing mental health issues among law enforcement officers. In addition, recruitment and retention has been a challenge for most agencies. By addressing police officers mental health, a department can develop healthy and more resilient officers. This benefits the officer, their family, and ultimately the citizens served by the officer.